PENDIDIKAN KARAKTER DENGAN TELAAH REVOLUSI MENTAL DALAM KONTEKS PENDIDIKAN ISLAM - FIRDAUS, ANDRIAN (EDUCATIONAL : Jurnal Inovasi Pendidikan & Pengajaran, 2024)
Mental Revolution is interpreted as a change in mindset in national life. Mental revolution does not simply rely on good intentions, but must take into account structural changes in societal interactions. In the realm of Islamic education, mental revolution must consider the structure of meaning, domination and legitimacy. These three things condition the mindset of Islamic education practitioners, the Islamic Education System, and the structure of Islamic education institutions themselves. The orientation of change as a result of implementing the mental revolution must be shown in the form of improving educational services for the welfare of society. Islamic educational institutions are expected to be able to explain injustice, arbitrariness and enable people to view, feel, think and act more rationally and wisely. ABSTRAKRevolusi Mental dimaknai sebagai sebuah perubahan mindset (pola pikir) didalam kehidupan berbangsa. Revolusi mental tidak cukup mengandalkan niat baik, namun harus memperhitungkan perubahan struktural dalam interaksi masyarakat. Di ranah pendidikan Islam, revolusi mental harus mempertimbangkan struktur pemaknaan, dominasi, dan legitimasi. Ketiga hal ini mengkondisikan pola pikir pelaku pendidikan Islam, Sistem Pendidikan Islam, dan struktur lembaga pendidikan Islam itu sendiri. Orientasi perubahan sebagai dampak dari implementasi revolusi mental harus ditunjukkan dengan wujud berupa peningkatan pelayanan pendidikan demi kesejahteraan masyarakat. Lembaga Pendidikan Islam diharapkan mampu mengurai tentang ketidakadilan, kesewenangan dan membuat manusia dalam memandang, merasa, berfikir, dan bertindak secara lebih rasional dan bijaksana.